Theological Study of Worship Singing as A Confession of Faith For Members of The GKI Victori Kehiran Congregation In Jayapura - Serli Patasik (Journal Research of Social Science, Economics, and Management, 2022)
Song is an integral part of the whole series of worship of the people in worship as a confession of faith, an expression of joy and thanksgiving, surrender and confession of sin. The Church in all its ministries continues the offering of chants in tone and motion, Music has the ability to include people in mystery. But music can also be a trial for man, if God is no longer the center of worship it means that the heart is separated from the heart so that the heart stops praising God and the chants chanted are only for the glory of man. The essence of singing in worship lies in the recognition of the majesty of God as the creator of the universe and the savior for human life. This recognition is experienced directly by all members of the congregation through the availability of natural resources, namely the fertility of the land enjoyed by the entire community, giving birth to a confession of faith thanks to the intervention of God we experienced all of this. This expression of faith is often sung through singing during worship in the form of congregational singing, choir or vocal group and solo. The song itself is located in everyone's heart so the singing is an offering of the tone of life that must be united and confirmed with the offering of the tone of the heart in worship because life is a beautiful song for the glory of God. Qualitative research methods with a triangulation approach are used to find out the extent to which the congregation of GKI Victori Kehiran Satu Sentani members interpret singing during worship as a confession of faith, so that the real singing is a daily pattern of life as a song for the glory of God.